2015
DOI: 10.1371/journal.pcbi.1004561
|View full text |Cite
|
Sign up to set email alerts
|

Signaling and Adaptation Modulate the Dynamics of the Photosensoric Complex of Natronomonas pharaonis

Abstract: Motile bacteria and archaea respond to chemical and physical stimuli seeking optimal conditions for survival. To this end transmembrane chemo- and photoreceptors organized in large arrays initiate signaling cascades and ultimately regulate the rotation of flagellar motors. To unravel the molecular mechanism of signaling in an archaeal phototaxis complex we performed coarse-grained molecular dynamics simulations of a trimer of receptor/transducer dimers, namely NpSRII/NpHtrII from Natronomonas pharaonis. Signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 88 publications
(159 reference statements)
2
27
0
Order By: Relevance
“…In the CheA “on” state, the protein interaction region adopts a dynamic state, which changes to a static state in the “off” state. Similar results were obtained for the archaeal phototaxis receptor/transducer complex . The allosteric coupling of these dynamic transitions into hexagonal arrays is thought to occur through a unique interface interaction between CheW and the P5 domain of CheA .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the CheA “on” state, the protein interaction region adopts a dynamic state, which changes to a static state in the “off” state. Similar results were obtained for the archaeal phototaxis receptor/transducer complex . The allosteric coupling of these dynamic transitions into hexagonal arrays is thought to occur through a unique interface interaction between CheW and the P5 domain of CheA .…”
Section: Discussionsupporting
confidence: 75%
“…). Signal transfer from the membrane and activation of CheA is thought to follow an alternating static–dynamic mechanism (, reviewed in ). In the CheA “on” state, the protein interaction region adopts a dynamic state, which changes to a static state in the “off” state.…”
Section: Discussionmentioning
confidence: 99%
“…Other TCS TM sensors, chemo-and photo-receptors, have domain organization similar to that of sensor histidine kinases as they possess the sensor module, TM and HAMP domains, but lack the autokinase module and control separate kinase protein (CheA) via the kinase control module ( Figure S1). Also, the core functional unit of chemoreceptors and phototaxis systems is not a dimer but a trimer of dimers (10)(11)(12), which may then pack into higher-order oligomeric assemblies (13).…”
Section: Main Text: Introductionmentioning
confidence: 99%
“…The first reaction in this photocycle is the photochemical isomerization of the retinal from the all-trans to the 13-cis form, in association with the generation of intermediate K. Proton migration from the Schiff base to Asp75 leads to the L-to-M transition, coinciding with the proton release at the extracellular side if the sensor is not complexed with its cognate transducer, NpHtrII. During the long-lived M-state, helix F moves outward and induces a downstream conformational change in the tightly coupled transmembrane helix TM2 of NpHtrII, which, in turn, transmits the signal further to the intracellular two-component pathway, which modulates the swimming behavior of the cell (30)(31)(32)(33) In our previous paper, we reported the assembly of NpSRII/ NpHtrII in SMALPs and showed that the NpSRII/NpHtrII complex retained its structural integrity as a native-like 2:2 dimer with the distance between spin labels bound at position 159 of NpSRII corresponding to the "V"-shaped conformation found in the crystal structure (25,34). Resonance Raman spectroscopy data confirmed that NpSRII reconstituted in SMALPs preserved the light-sensitive all-trans configuration of its retinal chromophore (25).…”
Section: Introductionmentioning
confidence: 97%
“…In our previous paper, we reported the assembly of Np SRII/ Np HtrII in SMALPs and showed that the Np SRII/ Np HtrII complex retained its structural integrity as a native‐like 2:2 dimer with the distance between spin labels bound at position 159 of Np SRII corresponding to the “V”‐shaped conformation found in the crystal structure . Resonance Raman spectroscopy data confirmed that Np SRII reconstituted in SMALPs preserved the light‐sensitive all‐trans configuration of its retinal chromophore .…”
Section: Introductionmentioning
confidence: 99%